Two sides of the story: bridging organizational and individual resilience - a qualitative study - Hilda Bø Lyng; Colleen Cheek; Cecilie Haraldseid-Driftland (BMC Health Services Research)
Abstract Background In resilience literature, champions are recognized as key organizational resources. Yet, their willingness to take on these roles and contribute extra efforts is rooted in autonomous motivation. This study aims to contribute understanding of both sides of this resilience story through the exploring of the motivation of champions found to contribute to organizational resilience in healthcare. Methods The empirical setting for this study includes eight different sites (two hospitals, five nursing homes and one home healthcare service) entailing interviews and observations of 55 healthcare informants (leaders and workers). Analysis of collected qualitative interviews through a deductive -inductive thematic analysis, using Self-determination Theory as an a priori framework for the deductive analysis. Results The importance of fostering connection among team members as well as between team members and leaders, offering flexibility to the champion to manage their role, and brokering relationships among teams or departments were illuminated. Conclusions Through the exploration of champions’ autonomous motivation for acting as organizational champions to ensure resilient performance in healthcare organizations, this study provides a more holistic picture where both sides of the story can be understood. Such holistic knowledge of champions is key to understand how to identify, support and maintain champions in their role to lay the groundwork for resilient performance in healthcare.